Physical health of schoolchildren aged 14-15 years old under the influence of differentiated education - I.P. Masliak; M.A. Mameshina (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Aim: to determine the dynamics of indicators of schoolchildren physical health under the influence of a multilevel system of differentiated education. Material and methods: The study involved schoolchildren (n = 148, age 14-15 years). Two control groups and two experimental groups were formed. Quantitative assessment of physical health was carried out according to 5 indices. Results: a low level of physical health of schoolchildren is established. The influence of the means of a multilevel system of differentiated education on the individual level of physical health of schoolchildren is determined. The most susceptible systems of the organism are determined to influence the differentiated training. An improvement in the adaptive capacity of the cardiovascular system during the recovery period after standard physical activity was revealed. Conclusions: The marked decrease in the heart rate at rest and blood pressure is evidence of a better state of adaptation mechanisms. A significant increase in the vital capacity of the lungs and the delay in breathing testifies to the improvement of the functional capabilities of the respiratory system and the body's resistance to hypoxic phenomena. Improvement in the development of strength, speed, speed endurance of the muscles of the back and abdominal press indicates an increase in the specific intensity of the performed work.